ANALISIS SWOT DALAM MENINGKATKAN DAYA SAING PRODUK (CV. JENANG MUBAROK KUDUS) - Ilham Haflawi Setiawan; Edy Dwi Kurniati; Nunuk Supraptini (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
Competitiveness is the ability to show better, faster or more meaningful results. The capabilities in question are the ability to strengthen its market share, the ability to connect with the environment, the ability to continuously improve performance, the ability to establish a profitable position. according to company conditions.The theory used is competitiveness and SWOT analysis, competitiveness according to Kotler and Armstrong (2008), defines competitive advantage as an advantage over competitors that is achieved by offering greater value to consumers, either through lower prices or by providing more benefits. According to David (2010), SWOT analysis defines the analytical tools used to compile strategic factors based on the strengths, weaknesses, opportunities and threats owned by the company.The type of research used in this research is descriptive qualitative. The population and samples were selected using a purposive sampling technique. The samples used in this study were people who were considered to know about CV's business conditions. Jenang Mubarok, totaling 7 people. The research method used is documentation, interviews, and questionnaires. The data analysis technique used is SWOT analysis which includes qualitative SWOT analysis, IFE matrix, EFE matrix and grand strategy matrix.The results of the analysis show that the business position based on the qualitative SWOT analysis is in the business position with the ST strategy, which is a combination of strategy with strength in dealing with threats. The results of the calculation of the Grand Strategy Matrix are strengths and weaknesses (S-W: = 1.86-1.83 = 0.03) so that it has a positive difference of 0.03, while for opportunities and threats (O-T: = 1.69-1.75 = -0.06) so it has a negative difference ofBased on the results of the analysis of the Grand Strategy Matrix, it shows that the business is in quadrant II, the appropriate strategy is concentric diversification and the ST strategy, namely to maintain strength in the face of threats, maintain quality products in the future so that consumers believe in jenang nubarok, add new products to win product competition, looking for cheaper raw materials to make jenang able to sell cheap prices, creating a copyright for the packaging of mubarok jenang products so that not many competitors imitate the product packaging